Respuesta :
Answer with explanation:
The given equation is
[tex]-4 -\frac{2 x}{3}= -6\\\\{\text{adding 4 on both sides}}\\\\ -4 -\frac{2 x}{3}+4= -6+4\\\\\frac{-2 x}{3}=-2[/tex]
Multiplying both sides by[tex]\frac{-3}{2}[/tex]
[tex]\frac{-2x}{3}*\frac{-3}{2}=-2* \frac{-3}{2}\\\\ x=3[/tex]
You can get the result by dividing both side of equation by [tex]\frac{-2}{3}[/tex]
The Correct Options are
Option A: After adding 4 to both sides, the equation is [tex]\frac{-2 x}{3}= -2[/tex]
Option (C.) The equation can be solved for x using exactly one more step by multiplying both sides by -3/2.
Option (D.) The equation can be solved for x using exactly one more step by dividing both sides by -2/3.